Isolation and fixation of the sex-linked barring feather gene from white leghorn for chick sexing - Ganxian Cai; Tianlan Xia; Tianqi Shao; Hesham Y.A. Darwish; Jiansheng Xu; Xuemei Deng; Junying Li (Poultry Science)
The White Leghorn chicken is a renowned high-yielding egg-laying breed, frequently utilized in hybrid breeding programs for the modification of egg production traits. However, the plumage color genes carried by White Leghorns, particularly the sex-linked barring feather gene, have rarely been exploited in breeding practices. Progeny resulting from crosses with White Leghorns predominantly exhibit white plumage due to the dominant white feather gene, which epistatically masks other feather colors. In this study, White Leghorns were reciprocally crossed with Dongxiang Black-Feathered Blue-Shelled Egg Chickens (DBBC), and the F1 generation exhibited white plumage in all individuals. In the F2 generation, feather color segregated into black, mottled, and barred patterns. Analysis revealed that the segregation of the barred plumage pattern followed a Z-linked inheritance model. In previously reported polymorphisms in the CDKN2A gene associated with barred feather patterns, we identified that only SNP4 was applicable for barring gene identification in this population. We also analyzed the correlation between the barring gene genotype and the color depth phenotype of barred feathers in adult roosters. The accuracy of identifying non-deeply barred roosters as homozygous for barring gene was 98.2 %. Population testing confirmed that the barring gene originated from the White Leghorn population. When barred hens derived from White Leghorns were crossed with black-feathered roosters, the accuracy of sex identification based on the barred feather phenotype in chicks was only 89.98 %. Two primary factors contributed to the reduced accuracy. First, two types of mottled feather phenotypes displayed epistatic effects over the barred phenotype, masking it in chicks. By excluding mottled chicks, the accuracy of sex identification increased to 93.99 %. Second, the barred feather pattern inherited from White Leghorns showed considerable variation in chicks, making identification difficult. By adopting the criterion of identifying the brightest white spot located along the midline of the chick's head, the accuracy of sex identification could be further improved. This study demonstrates that the sex-linked barring feather gene can be isolated from White Leghorn chickens and utilized for sex identification at hatch. In addition, White Leghorn chickens carry a wealth of other feather color genes that are masked by the dominant epistatic white feather gene. Crossing White Leghorn chickens with colored-feathered chickens can result in the segregation of novel feather colors, offering promising prospects for breeding applications.